Measuring Women's Self-help Group Sustainability: A Study of Rural Assam. (April 2019) - Das, Tiken; Guha, Pradyut
The Self-help Group Bank Linkage Programme (SHG-BLP) is now a major global microfinance programme in India with 8.7 million SHGs with deposit of over `195, 000 million and annual loan offtake of more than `470, 000 million. However, group sustainability is having a wider concern among donor agencies, practitioners, policymakers and academicians to achieve persistent benefit from SHGs in financial intermediation. The present study made an attempt to examine the status of group sustainability with the help of multidimensional sustainability index of SHGs (MDSI SHG ) by combining organizational, managerial and financial indicators of 60 SHGs in Assam. It was found that 95 per cent of SHGs positioned within the range of 'high' and 'moderate' MDSI SHG status and, therefore, may maintain their function well over a long period of time. Thus, the study recommends for enlargement of the scope of semiformal financial institutions (in our study: SHGs) in rural areas of Assam only for income-generating activities with proper market linkages. There is a scope to regenerate and validate the findings using relatively large sample size with SHGs of varied socio-economic background.